Introduction to business adminstration - GHERZOULI, Imane (Setif1 University Ferhat ABBAS , Faculty of Economics , Business and management Sciences , Department of Finance and Accounting, 2026)
This handout is designed as a comprehensive guide for second-year students across all specializations in the Faculty of Economic Sciences. It systematically covers foundational definitions, explores the evolution of management thought, and examines both classical and contemporary schools of management. By integrating theoretical perspectives with practical analysis, the handout aims to equip students with the knowledge and critical thinking skills necessary to understand the complexities of management and business administration. Throughout the chapters, students will encounter key definitions, fundamental principles, and comparative analyses of major management theories. Special attention is given to the distinction between public and business administration, the importance and objectives of business administration, and the evolving roles and functions of managers in modern organizations. The textbook also provides a critical evaluation of classical, behavioral, and modern management schools, offering insights into their relevance and application in today's dynamic business environment.
For second year students all specializations